Coordination of spatial and temporal laser beam profile towards ultra-fine feature fabrication in laser powder bed fusion (Journal of Additive Manufacturing Technologies, 2022)
Laser powder bed fusion (LPBF) is a metal additive manufacturing technology that provides high shape and application flexibilities. Although dimensional flexibility is high in theory thanks to the non-contactless micro range processing tool (i.e., laser beam) and powder, the fabrication robustness of thin and ultra-thin features (dnominal?200 ?m) is still a challenge for the technology. In particular, geometrical fidelity and dimensional accuracy problems have been raising towards the ultra-thin fabrication segment. Although there were different studies that presented solutions for robust and sustainable fabrication strategy in ultra-thin segment in the literature, the vast majority of them focused on process itself directly, and the technological feasibility of the LPBF systems was not considered. However, without considering technological feasibility of the LPBF systems, the presented solutions in the literature are far from providing solid basis and they may mislead the users in the case of direct application. In this sense, this study mainly focused on the scanning capability of the systems for features under 200 µm dimensional range with temporal and spatial laser beam management in the case of conventional scanning strategy (contour and hatch). For this purpose, the fabrication process reduced to the two dimensions (scanning region) via the laser marking tests, and custom laser parameters, which are provided by the industrial grade open architecture LPBF system, has been used. Here, it has been reported that two different errors related to scanning performance and process parameters for continuous and pulsed wave laser emission modes, separation, and compensation of these two errors, and investigation methodology for technological feasibility of the LPBF machines. Moreover, in the pulsed wave laser emission mode, two linear parameters have been presented to optimize spatial energy distribution. Considering the results coming from the practical observations and measurements, it is possible to indicate that the technological feasibility of the utilized LPBF system should be key concern before laser or scan related parameters optimization. The results show that if correct scanning parameters have been selected in the technological feasibility window of the system, scan trajectories based on conventional hatching method can be carried out with sufficient geometrical accuracy.
Keywords: LPBF; dimensional feasibility; temporal-spatial beam control; geometrical fidelity; ultra-thin features